Is neural hyperpolarization by cathodal stimulation always detrimental at the behavioral level? - Pirulli, Cornelia; Fertonani, Anna; Miniussi, Carlo (Frontiers in Behavioral Neuroscience, 2014)
Cathodal transcranial direct current stimulation (c-tDCS) is usually considered an inhibitory stimulation. From a physiological perspective, c-tDCS stimulation induces hyperpolarization at the neural level. However, from a behavioral perspective, c-tDCS application does not always result in performance deterioration. In this work, we investigated the role of several important stimulation parameters (i.e., timing, presence of pauses, duration and intensity) in shaping the behavioral effects of c-tDCS over the primary visual cortex. In Experiment 1, we applied c-tDCS at two different times (before or during an orientation discrimination task). We also studied the effects of pauses during the stimulation. In Experiments 2 and 3, we compared different durations (9 minutes vs. 22 minutes) and intensities (0.75 mA vs. 1.5 mA) of stimulation. c-tDCS applied before task execution induced an improvement of performance, highlighting the importance of the activation state of the cortex. However, this result depended on the duration and intensity of stimulation. We suggest that the application of c-tDCS induces depression of cortical activity over a specific stimulated area; but to keep reactivity within given limits, the brain react in order to restore the equilibrium and this might result in increased sensitivity in visual performance. This is a further example of how the nervous system dynamically maintains a condition that permits adequate performance in different environments.